REVITALISASI PASAR GUNUNG PARMAN SEBAGAI UPAYA MENINGKATKAN FUNGSI PASAR DI RT 35 KELURAHAN KARANG JOANG - Putra, Rulliannor Syah; Amir, Supratiwi; Syaputra, Eko Agung; Siahaan, Axel Andrewilson; Rahma, Firdha Amalia Noor (Jurnal Abdi Insani, 2024)
Gunung Parman Market RT 35 Karang Joang Balikpapan is a market that residents used to sell, but because it was not maintained and there was a lack of interest, this market became neglected. Competition with the night market which operates every Wednesday night is also the cause of the lack of interest, the merchandise is more complete and there are lots of visitors. This causes the attractiveness of Gunung Parman Market to decrease and the building to become increasingly neglected and damaged. The aim of this community service activity is to rebuild the dead market and then revive RT 35's trading activities while improving the community's economy. The method for implementing the activities carried out is Participatory Action Research (PAR), this approach is oriented towards community empowerment. The flow of implementing community empowerment activities starts from a location survey, then collecting primary and secondary data, gathering opinions, design, market development and promotion. The results obtained during the activity were an increase in solidarity between communities, community understanding and knowledge. Solidarity or togetherness was achieved during the construction of the physical market building which was carried out during holidays and even at night. The community is more united because this service is a means to gather and express creativity. The topography of the market land is quite sloping so creativity is needed so that the market can still be built and make things easier for consumers. Achieving knowledge about market design planning through joint discussions, knowledge about market promotion through social media and increasing the spirit of mutual cooperation in building markets. Therefore, it is necessary to revitalize the market as a form of increasing the value and function of the RT 35 Karang Joang Village market.